STRATEGY ANALYSIS OF COOPERATIVE-BASED SEAWEED BUSINESS DEVELOPMENT IN TAKALAR DISTRICT - Asri Asri; Rego Devila; Hamran Hamran (International Journal of Economy, Education and Entrepreneurship, 2022)
The purpose of this study was to analyze the role of cooperative institutions in terms of capital, human resource development (HR), seaweed business management, and marketing for seaweed business development in the Takalar Regency. This research is qualitative research with data collection techniques through observation, interviews, and documentation. The results of the research based on the SWOT analysis show that the cooperative-based seaweed business development strategy in Takalar Regency can be done by looking at potential as strengths and opportunities, in addition to obstacles as weaknesses and threats. Its strengths are: fast production management, a very large area of ​​land, the existence of group organization by cooperatives, and the quality of the seaweed produced is very good; The opportunities (opportunities) are: high demand for seaweed, cooperatives maintaining good relations with the seaweed processing industry and a positive image of seaweed from Takalar Regency. While the weaknesses (weaknesses), namely: lack of capital in business development, production results are not optimal and it is difficult for seaweed farmers to get quality seeds; and threats, namely: fluctuating prices and other areas that have the potential to produce seaweed with good quality